2020
DOI: 10.5582/ddt.2020.03046
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lymphocyte Kv1.3-channels to suppress cytokine storm in severe COVID-19: Can it be a novel therapeutic strategy?

Abstract: cytokine storm, lymphocyte, chloroquine In the midst of a pandemic, finding effective treatments for coronavirus disease 2019 (COVID-19) is the urgent issue. In "chronic inflammatory diseases", the overexpression of delayed rectifier K + -channels (Kv1.3) in leukocytes is responsible for the overactivation of cellular immunity and the subsequent cytokine storm. In our previous basic studies, drugs including chloroquine and azithromycin strongly suppressed the channel activity and pro-inflammatory cytokine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Exorbitant inflammation evokes a serious of expanded cascade reaction, leading to systemic inflammation and multiple organ dysfunction syndromes [ 9 , 36 ]. Other research groups have revealed that cytokine storm is observed in COVID-19 patients and inflammation suppression alleviated the severity of COVID-19 [ 37 , 38 ]. In our present research, IL-17 was also shown to be prominently and positively related with inflammatory cytokines in CAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exorbitant inflammation evokes a serious of expanded cascade reaction, leading to systemic inflammation and multiple organ dysfunction syndromes [ 9 , 36 ]. Other research groups have revealed that cytokine storm is observed in COVID-19 patients and inflammation suppression alleviated the severity of COVID-19 [ 37 , 38 ]. In our present research, IL-17 was also shown to be prominently and positively related with inflammatory cytokines in CAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine has been in use as an antimalarial agent for over 5 decades. It also suppresses the activity of mammalian delayed rectifier K + channels (Kv1.3) in leukocytes and lymphocyte production of pro-inflammatory cytokines ( 58 ). Chloroquine has anti-inflammatory and immunomodulatory properties and is used to treat autoimmune diseases including rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Ion Channel Blockers With Potential As Anti-tuberculosis Agentsmentioning
confidence: 99%
“…For the development of idiopathic pulmonary fibrosis, several growth factors, such as transforming growth factor (TGF)-β, vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF) and epidermal growth factor (EGF), are generally considered to be responsible (7,8), since these growth factors promote the profibrogenic process of the lung after injury. For the development of "post-COVID-19" pulmonary fibrosis, cytokine storm, which is characterized by the over-activation of leukocytes and the uncontrolled secretion of proinflammatory cytokines, is additionally thought to be responsible (9,10). These cytokines impair the recovery process from the lung injury and stimulate the activity of fibroblasts to produce collagen, and thus promote the progression of pulmonary fibrosis (11).…”
Section: Itsuro Kazama *mentioning
confidence: 99%
“…Taking into account such pharmacological properties of these drugs, they may also be useful in the treatment of post-COVID-19 pulmonary fibrosis, in addition to their usefulness in suppressing cytokine storm (9).…”
Section: Itsuro Kazama *mentioning
confidence: 99%